Effect of Autologous Expanded Bone Marrow Mesenchymal Stem Cells or Leukocyte-Poor Platelet-Rich Plasma in Chronic Patellar Tendinopathy (With Gap >3 mm): Preliminary Outcomes After 6 Months of a Double-Blind, Randomized, Prospective Study. Issue 6 (May 2021) - Rodas, Gil; Soler-Rich, Robert; Rius-Tarruella, Joan; Alomar, Xavier; Balius, Ramon; Orozco, Lluís; Masci, Lorenzo; Maffulli, Nicola
Background: Patellar tendinopathy is common. The success of traditional management, including isometric or eccentric exercises combined with shockwave therapy and even surgery, is limited. Therefore, it is important to determine whether biological treatments such as ultrasound-guided intratendinous and peritendinous injections of autologous expanded bone marrow mesenchymal stem cells (BM-MSCs) or leukocyte-poor platelet-rich plasma (Lp-PRP) improve clinical outcomes in athletic patients with patellar tendinopathy. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A prospective, double-blinded, randomized, 2-arm parallel group, active controlled, phase 1/2 single-center clinical study was performed in patients who had proximal patellar tendinopathy with a lesion >3 mm. A total of 20 participants (age 18-48 years) with pain for >4 months (mean, 23.6 months) and unresponsive to nonoperative treatments were randomized into 2 groups. Of these, 10 participants were treated with BM-MSC (20 × 10 6 cells) and 10 with Lp-PRP. Both groups performed the same postintervention rehabilitation protocol. Outcomes included the Victorian Institute of Sport Assessment for pain (VISA-P), self-reported tendon pain during activity (visual analog scale [VAS]), muscle function by dynamometry, tendon thickness and intratendinous vascularity by ultrasonographic imaging and Doppler signal, ultrasound tissue characterization (UTC) echo type changes, and magnetic resonance imaging (MRI) T2-weighted mapping changes. Participants were followed longitudinally for 6 months. Results: The average VAS scores improved in both groups at all time points, and there was a significant reduction in pain during sporting activities ( P < .05). In both groups, the average mean VISA-P scores at 6 months were significantly increased compared with baseline (66 BM-MSC group and 72.90 Lp-PRP group), with no significant differences in VAS or VISA-P scores between the groups. There were statistically significant greater improvements in tendon structure on 2-dimensional ultrasound and UTC in the BM-MSC group compared with the Lp-PRP group at 6 months. Similarly, the BM-MSC group demonstrated significant evidence of restoration of tendon structure on MRI compared with the Lp-PRP group at 6 months. Only the participants in the BM-MSC group showed evidence of normalization of tendon structure, with statistically significant differences between the groups on T2-weighted, fat-saturated sagittal and coronal scans and hypersignal in T2-weighted on spin-echo T2-weighted coronal MRI scan. Both treatments were safe, and no significant adverse events were reported in either group. Conclusion: Treatment with BM-MSC or Lp-PRP in combination with rehabilitation in chronic patellar tendinopathy is effective in reducing pain and improving activity levels in active participants. Participants who received BM-MSC treatment demonstrated greater improvement in tendon structure compared with those who received Lp-PRP. Registration: 2016-001262-28 (EudraCT identifier); NCT03454737 (ClinicalTrials.gov identifier)